The effect of rapid maxillary expansion on the lower dental arch - Afifi, Hussam (My University, 2001)
Bu çalışmanın amacı, hızlı maksiller genişletmenin alt diş arkına olan etkisinin araştırılmasıdır. Çalışma grubu Marmara Üniversitesi Diş Hekimliği Fakültesi Ortodonti A.B.D na başvuran hastalar arasından seçilen 15 bireyden oluşmuştur (6 erkek,9 kız ). Sadece tedavi planı maksiller genişletme gerektiren hastalar çalışmaya dahil edildi. Alt daimi kaninler sürmeden önce normal büyümeye bağlı olarak alt ark genişliğinde meydana gelebilecek artışı elimine etmek için alt daimi kaninleri sürmüş bireyler seçildi. Genişletme apareyini takmadan önce, genişletmeden hemen sonra ve 3 aylık pekiştirme dönemi sonunda posteroanterıer röntgenler ve model fotokopileri alındı. Sonuçlar, alt intermolar genişliğinde 1.03 mm' lik, alt interkanin genişliğinde 0,53 mm' lik önemli artış ve alt ark uzunluğunda da 0.56 mm'lik önemli azalma olduğunu ortaya koymuştur. Mandibuladaki interkanin ve intermolar genişliğindeki değişikliklerle maksilladaki bu değişiklikler arasında bir korelasyon bulunamadı.

The aim of this study is to investigate the effects of rapid maxillary expansion on the lower dental arch. This study involved 15 patients (6 male and 9 female), who were selected from clinical in take of the orthodontic department in the Dental Faculty of Marmara University. Patients were chosen only if there was indication of the treatment plan or the treatment recorded that the maxillary expansion was a goal of treatment. In all patients, lower permanent canines were present in order to eliminate any increase of the lower inter-arch width that could be expected from normal growth before lower canine eruption. Posteroanterior radiographs and model photocopies were obtained before placing the expansion appliance, directly after expansion, and after three months of retention period. The result showed that there was significant increase of 1.03 mm in lower intermolar width, significant increase of 0.53 mm in lower intercanine width, and significant decrease of 0.56 mm in lower arch length. No correlations were found between the changes in mandibular intercanine and intermolar widths and the changes in maxillary intercanine and intermolar widths.
Keywords: Diş Hekimliği-tedavi; Ortodonti